TEXNIK DETALLARNI MURAKKABLIK DARAJALARIGA AJRATISH YOLLARI VA ULARNI TALABALARGA O’RGATISH USULLARI - Avezov, B.; Nazarbekov, Q.; Pirniyozova, M. (SCIENCE and SOCIETY, 2017)
The article is devoted to the study of the methods of definition of various products used in manufacture of technical details, mechanisms of machines, degree of complexity, form, structure of bodies having complex geometrical surfaces in the objects of construction.